Take a piece of peace, please - Panayides, Angelos (My University, 2023)
(4)ANOTHER LIFE Posters dedicated to the recent changes in the world, both negative and positive IBCC / INTERNATIONAL BIENNALES COORDINATING COMMITTEE IMAGE / INTERNATIONAL MEETING OF GRAPHIC EVENTS
Keywords: international, biennale, poster, graphic, design, exhibition, catalogue